Broadband light active MTCNQ-based metal–organic semiconducting hybrids for enhanced redox catalysis. (December 2018) - Mohammadtaheri, Mahsa; Ramanathan, Rajesh; Walia, Sumeet; Ahmed, Taimur; Weerathunge, Pabudi; Anderson, Samuel R.; Field, Matthew R.; Dekiwadia, Chaitali D.; O'Mullane, Anthony P.; Gaspera, Enrico Della; Bhaskaran, Madhu; Sriram, Sharath; et al.
Graphical abstract: Highlights: A simple liquid-phase strategy to fabricate high aspect ratio nanorod arrays of M@MTCNQ (where M = Cu or Ag) hybrids on 3D cotton fibrils as template is shown. The broadband light absorption property of the hybrids across the visible and infrared region of the solar spectrum is established. The importance of using 3D templates to grow organic semiconductors for photoactive reductive catalysis is shown. The importance of efficient charge transfer at the catalyst/reactant interface as well as at the metal/semiconductor interface on enhancing the photocatalytic rates is established. Abstract: Efficient harvesting of solar light is highly desirable for a wide range of applications, including photocatalysis and energy conversion. However, traditional semiconducting metal oxide photocatalysts are typically effective only under UV irradiation while metal–metal oxide hybrids can utilize the UV as well as the visible component of the solar light. In this article, we fabricate hybrids of metal–7, 7, 8, 8-tetracyanoquinodimethane (TCNQ) on cotton fibres as a supporting three-dimensional (3D) template for photo-reductive catalysis. These materials extend the absorption of light from the visible to infrared region, thereby allowing the use of over 95% of solar irradiation. We demonstrate the ability of these materials to harvest light across a broad wavelength range by utilizing them as highly active materials for reductive photocatalysis. The mechanism of the underlying charge-transfer phenomena under different photo-excitation conditions reveals a photo-illumination induced redox process at the catalyst/reactant interface resulting in superior catalytic efficiency.